2021
DOI: 10.1167/iovs.62.9.27
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Retinal Connexins Cx36 and Horizontal Cell Coupling in Emmetropization in Guinea Pigs

Abstract: The purpose of this study was to determine whether retinal gap junctions (GJs) via connexin 36 (Cx36, mediating coupling of many retinal cell types) and horizontal cell (HC-HC) coupling, are involved in emmetropization. METHODS.Guinea pigs (3 weeks old) were monocularly form deprived (FD) or raised without FD (in normal visual [NV] environment) for 2 days or 4 weeks; alternatively, they wore a −4 D lens (hyperopic defocus [HD]) or 0 D lens for 2 days or 1 week. FD and NV eyes received daily subconjunctival inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
1
5
1
Order By: Relevance
“…After 2-weeks and 4-weeks FDM, relative myopic shifting of refractive errors, elongation of axial length, and vitreous chamber depths observed in the treated eyes were consistent with published parameters of FDM guinea pigs (Lu et al, 2006;Zhi et al, 2021). However, a larger myopic shift (−11.00 ± 0.75 D) in terms of refractive error was found in a previous study in 4-weeks FDM guinea pigs (Wu et al, 2014).…”
Section: Refractive Error and Ocular Dimensions Changessupporting
confidence: 88%
“…After 2-weeks and 4-weeks FDM, relative myopic shifting of refractive errors, elongation of axial length, and vitreous chamber depths observed in the treated eyes were consistent with published parameters of FDM guinea pigs (Lu et al, 2006;Zhi et al, 2021). However, a larger myopic shift (−11.00 ± 0.75 D) in terms of refractive error was found in a previous study in 4-weeks FDM guinea pigs (Wu et al, 2014).…”
Section: Refractive Error and Ocular Dimensions Changessupporting
confidence: 88%
“…RGCs and horizontal cells have been studied under the conditions of emmetropization and myopia progression in animal models. Altered cell-cell coupling by the gap junction protein connexin 36 in horizontal cells in the inner plexiform layer (IPL) has been found to play important roles in emmetropization and FDM in guinea pigs, as the uncoupling agent 18-β-GA induces myopic shifts and FDM decreases total connexin 36 levels and phosphorylation ( Zhi et al, 2021 ). In addition, a recent study showed that stimulation of RGCs expressing neuropsin (OPN5) with violet light prevented experimental myopia in mice ( Jiang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The retina is a thin layer of complex neural tissue that receives light-stimuli and processes visual signal, and transmitted signal to the sclera. Numerous studies have suggested the retina playing important roles in the pathology in myopia, such as circuiting electrical and chemical synapses ( Zhi et al, 2021 ). Moreover, lncRNAs play pathogenic roles in several retinal diseases, such as the lncRNA XIST and nuclear paraspeckle assembly transcript 1, which play roles in diabetic retinopathy ( Li, 2018 ; Dong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…All mice were handled and maintained in the animal facility of the School of Ophthalmology and Optometry at Wenzhou Medical University as authorized by the Institutional Animal Care and Use Committee of Wenzhou Medical University. 51 , 52 All animal experiments were performed in accordance with the ARVO Statement for the Use of Animals in Ophthalmic and Vision Research.…”
Section: Methodsmentioning
confidence: 99%